2018
DOI: 10.1177/0194599818797605
|View full text |Cite
|
Sign up to set email alerts
|

Hypopharyngeal Cancer Treatment Delays: Benchmarks and Survival Association

Abstract: Objective To characterize treatment delays in hypopharyngeal cancer, identify factors associated with delays, and associate delays with overall survival. Study Design Retrospective cohort. Setting Commission on Cancer hospitals nationwide. Subjects and Methods We included patients in the National Cancer Database who were treated for hypopharyngeal cancer with primary radiation, concurrent chemoradiation, or induction chemotherapy and radiation. We identified median durations of diagnosis to treatment ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 73 publications
3
32
0
Order By: Relevance
“…However, other studies by Morse et al 27‐29,34,35 to characterize treatment delays with OS on HNSCC using also NCDB from year 2004 to 2013 yielded variable results. According to these cohorts, the diagnosis to treatment initiation was not associated with poorer OS in oral cavity SCC, 37 primarily resected oropharyngeal SCC, 29 salivary gland cancer, 35 and hypopharyngeal cancer treated with induction chemotherapy 27 . Instead, treatment delays were associated with poorer survival only in hypopharyngeal cancer treated with primary radiation or chemoradiation 27 .…”
Section: Discussionmentioning
confidence: 97%
“…However, other studies by Morse et al 27‐29,34,35 to characterize treatment delays with OS on HNSCC using also NCDB from year 2004 to 2013 yielded variable results. According to these cohorts, the diagnosis to treatment initiation was not associated with poorer OS in oral cavity SCC, 37 primarily resected oropharyngeal SCC, 29 salivary gland cancer, 35 and hypopharyngeal cancer treated with induction chemotherapy 27 . Instead, treatment delays were associated with poorer survival only in hypopharyngeal cancer treated with primary radiation or chemoradiation 27 .…”
Section: Discussionmentioning
confidence: 97%
“…Compared to white patients, black patients experienced less timely care across all three treatment intervals that we studied. Multiple prior analyses have found black race to be associated with head and neck cancer treatment delays, as well as inferior local control and overall survival . A tendency to receive less timely care may underlie some of the disparities in oncologic outcomes for this population.…”
Section: Discussionmentioning
confidence: 99%
“…Of the multiple factors that may underlie prolonged DTS, care transitions appear to play a major role in sinonasal cancer. Patients in our study more commonly received treatment at a site other than the diagnosing facility (61%) compared to studies of salivary (33%), laryngeal (39%), or hypopharyngeal (43%) cancer using the same database. Such care transitions were among the strongest predictors of prolonged DTS.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] have reported the prognostic association of facility case volume on HNSCC outcomes and guideline adherence. To our knowledge, this is the first study to determine facility case volume thresholds for all HNSCCs.…”
Section: Discussionmentioning
confidence: 99%
“…The National Comprehensive Cancer Network guidelines specify that "outcomes are improved when patients with head and neck cancers are treated in highvolume centers." 2 and a rapidly expanding body of literature [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] supports this statement.…”
mentioning
confidence: 97%